2010
DOI: 10.1080/14786410802680902
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activities onEphedra nebrodensisTineo

Abstract: As a part of our endeavour to screen Mediterranean medicinal plants for various pharmacological activities, we evaluated antihistaminic, adaptogenic, anti-inflammatory, antinociceptive, hypotensive and locomotor properties, and antioxidant potential of Ephedra nebrodensis. (1)H-NMR spectroscopy was carried out to identify the plant metabolites, which confirmed the presence of ephedrinic skeleton alkaloids. The ethanol : acetone (1 : 1) extract exhibited dose-related antihistaminic, anti-inflammatory, antinocic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Finally, Ephedra nebrodensis, which has the lowest distribution, can be found in North Africa [56], Europe (▶ Fig. 2 e) [57], including Italy [58,59] and Spain [52], Morocco [60], and Algeria [61]. Here, we will focus on Moroccan Ephedra species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Ephedra nebrodensis, which has the lowest distribution, can be found in North Africa [56], Europe (▶ Fig. 2 e) [57], including Italy [58,59] and Spain [52], Morocco [60], and Algeria [61]. Here, we will focus on Moroccan Ephedra species.…”
Section: Resultsmentioning
confidence: 99%
“…A 1 : 1 ethanolic : acetone crude extract prepared from the aerial parts of a plant sample collected in Urzulei (Sardinia, Italy) has shown antioxidant and hypotensive effects, as well as antinociceptive and anti-inflammatory activities. The presence of ephredrine-type alkaloids was suspected [59]. The presence of ephedrine and pseudoephedrine (▶ Fig.…”
Section: Ephedra Fragilismentioning
confidence: 99%
“…It is reported that phenolic compounds possess free radical scavenging properties (Tabassum et al, 2017). E. nebrodensis has been also reported for its antioxidant potential (Ballero et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…DMSO was the vehicle used for the dissolution of plant extracts, and its final concentration in the cells was less than 0.2%. (18)(19)(20). The percentage change in viability was calculated according to the following formula: ((reading of extract/reading of negative control) − 1) × 100.…”
Section: Cell Viability Assay Mttmentioning
confidence: 99%